qanda-logo
search-icon
root-icon-orangeSímbolos
Problema
solution-image
– 6) $t\left(x^{2}=$ $3x+2\right)=\left(2x^{2}+$ 6x $4T\right)$ = ab) ) $\left(3x^{2}+8x$ $\left(2x^{3}-x^{2}$ $\left(x^{4}+5x^{3}$ $2x$ + $\right)=\left(x^{3}+3x^{2}$ - $xθ2$ - $3x2$ $5\pi ^{2}4$ $0x$ - 6) = d) c) $4$ + $-6x^{2}-2x+3\right)$ $\left(6x^{3}$ $2^{2}+4x+9\right)+\left(x$ $x^{2}-7x+10\right)-\bar{2x} 2+6\bar{x\right)} +6x^{3}-12\right)-x$ + $B\bar{x} ^{7}$ + $5x$ - $8\right)$ = - - - – $\left(x^{2}=4x$ =
Secundaria
Otra
Búsquedas: 146
Solución
answer-user-profile-image
Profesor de Qanda - dany
answer-reply-image